2016
DOI: 10.1186/s12906-016-1326-3
|View full text |Cite
|
Sign up to set email alerts
|

Perception of risk and communication among conventional and complementary health care providers involving cancer patients’ use of complementary therapies: a literature review

Abstract: BackgroundCommunication between different health care providers (conventional and complementary) and cancer patients about their use of complementary therapies affects the health and safety of the patients. The aim of this study was to examine the qualitative research literature on the perception of and communication about the risk of complementary therapies between different health care providers and cancer patients.MethodsSystematic searches in six medical databases covering literature from 2000 to 2015 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 48 publications
1
44
1
Order By: Relevance
“…The complementary therapists believed that to a lesser extent. However, the assumption that risk associated with many complementary modalities is indirect is in accordance with Fisher [13], Dantas [21], and Stub [17]. They found that the main risks associated with homeopathy and other complementary modalities were indirect; that is, related to the therapists and clinical practice rather than the medicine.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…The complementary therapists believed that to a lesser extent. However, the assumption that risk associated with many complementary modalities is indirect is in accordance with Fisher [13], Dantas [21], and Stub [17]. They found that the main risks associated with homeopathy and other complementary modalities were indirect; that is, related to the therapists and clinical practice rather than the medicine.…”
Section: Discussionmentioning
confidence: 82%
“…Moreover, more than half of the medical doctors and nurses neither discouraged nor encouraged the use of complementary modalities. Advice may depend on the situation, the medical doctor’s knowledge of the complementary therapy and cancer type [17]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Vanguard Study questionnaire was based on information retrieved from a literature review performed by our research group [16]. During a 7 month research stay in the US, TS participated in weekly meetings with SQ, JS, and TA, where the questions were discussed and refined with input from a reference group of US conventional and complementary providers.…”
Section: Methodsmentioning
confidence: 99%